2012
DOI: 10.1007/s10886-012-0068-z
|View full text |Cite
|
Sign up to set email alerts
|

Plant Volatiles Enhance Behavioral Responses of Grapevine Moth Males, Lobesia botrana to Sex Pheromone

Abstract: Plant volatiles play an important role in the lives of phytophagous insects, by guiding them to oviposition, feeding and mating sites. We tested the effects of different host-plant volatiles on attraction of Lobesia botrana males to the female-produced sex pheromone, in a wind tunnel. Addition of volatile emissions from grapevines or individual plant volatiles to pheromone increased the behavioral responses of L. botrana males over those to pheromone alone. At a low release rate (under-dosed) of pheromone, add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…Octenol is used as an aggregation pheromone in the sawtoothed grain beetle, Oryzaephilus surinamensis 42 and as a plant attractant in the black blowfly, Phormia regina 43, the legume pod borer, Maruca vitrata 44, the Grapevine Moth, Lobesia botrana 45, the European grape berry moths, Eupoecilia ambiguella 46 and the sandfly Lutzomyia longipalpis 47. It is also used as a compost attractant for the phorid fly, Megaselia halterata 48 and as an avoidance cue for the parasitoid Lariophagus distinguendus 49.…”
Section: Discussionmentioning
confidence: 99%
“…Octenol is used as an aggregation pheromone in the sawtoothed grain beetle, Oryzaephilus surinamensis 42 and as a plant attractant in the black blowfly, Phormia regina 43, the legume pod borer, Maruca vitrata 44, the Grapevine Moth, Lobesia botrana 45, the European grape berry moths, Eupoecilia ambiguella 46 and the sandfly Lutzomyia longipalpis 47. It is also used as a compost attractant for the phorid fly, Megaselia halterata 48 and as an avoidance cue for the parasitoid Lariophagus distinguendus 49.…”
Section: Discussionmentioning
confidence: 99%
“…The more difference in the chemical profiles of an herbivore host and its plant background, the more olfactory contrast generated, and the more detectable a host larva becomes (Hilker & McNeil, ). Similar observations have been reported for male moths (Light et al ., ; Deng et al ., ; Yang et al ., ; von Arx et al ., ) and parasitoids (Xu et al ., ) in which plant volatiles synergistically enhanced the detection of female sex pheromones. The relevance of plant volatiles as background odors in parasitoid host location has been discussed in previous studies (Mumm & Hilker, ; Schröder & Hilker, ; Beyaert et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Leaf acetate attracted male Grapholita molesta (Busck) in laboratory experiments (Varela et al., ) and increased the trapping efficiency of G. molesta sex pheromones in field experiments (Yu et al., ,b). Thus, leaf acetate was used as a potentiator for the sex pheromones of G. molesta (Yu et al., ,b) and also enhanced the attractive effect of Lobesia botrana (Denis & Schiffermüller) sex pheromones on males (Von Arx et al., , ). Our results indicated that unmated PFM males have higher EAG values than females to the optimum dose of leaf acetate.…”
Section: Discussionmentioning
confidence: 99%
“…1 suppressed PFM attraction to α‐farnesene, whereas it did not suppress PFM attraction to leaf acetate. Previous studies have revealed that α‐farnesene plays a crucial role in female detection and location of host plants (Landolt et al., ; Binder et al., ; Bengtsson et al., ; Witzgall et al., ), whereas leaf acetate plays a crucial role in female courtship and mating with males (Von Arx et al., , ; Yu et al., ,b). Jujube Protection No.…”
Section: Discussionmentioning
confidence: 99%